A new proposal for an offshore wind foundation for transitional waters. (November 2019) - Vieira, M.; Maciel, G.; Henriques, E.; Reis, L.
Abstract: Offshore wind energy is a renewable source with strong prospects of development, allowing both the reduction of greenhouse gas emissions and the promotion of technological progress. Nowadays, the top technological solution used in offshore wind foundations is the monopile, with a market share of more than 80%, due to its low-cost when compared to other technologies. Still, its use is limited to shallow waters (depths up to 30 m). Therefore, and for higher depths, other types of foundations should be considered. The authors of this work present a foundation concept for transitional waters with self-floating capability and suction pile embedment. This foundation is formed by a tripod, a transition piece and a variable number of floaters and the respective suction pile. The structure is self-floating and is transported to the installation site aided by tugboats. Under these circumstances, buoyancy and stability of the entire structure must be ensured. The suction piles can also be filled with air during port logistics, through reduction of the necessary port draft. When the structure arrives at the installation site, it submerges by filling the floaters, and the suction piles guarantee the correct attachment to the seabed. Regarding the developed structure, a modal analysis was made to compute its natural frequencies and mode shapes. Moreover, the structure behavior during transportation is evaluated using AQWA tools. The developed foundation was then validated for a certain number of cases defined by the current DNV-GL standard. Highlights: A new foundation concept for offshore wind conditions for transitional waters is proposed. The new structure has self-floating capability and a suction pile embedment is proposed. The new structure has the possibility to be transported to the installation site aided by tugboats. A modal analysis was carried out in order to compute the structure's natural frequencies and mode shapes. The developed foundation was validated for a certain number of cases defined by the current DNV-GL standard.